Handbook for communicating the Philippine centennial of 1998. - Philippines. National Centennial Commission (Pasig City National Centennial Commission, 1996)
A handbook that aims to help the communicator present history accurately, to use the 1998 Centennial of the Philippines to unify and harmonize the Filipinos' diverse cultural groupings and to encourage use of keywords and values to increase the public's recall and understanding of the National Centennial Commission's objectives.
The Philippine's National Centennial Commission (NCC) sees its communication efforts as out-of-classroom civic education with three components (1) recounting historical events accurately (2) inspiring values and character formation and (3) catalyzing responsible citizens.
This handbook helps anyone who crafts communication campaign to find nobleness and excellence in our culture, past and present and to value our sameness as well as our singularities. Communicating history is not so much talking about the past, as it reaffirming a people's belief in themselves so they can capably handle the now and the tomorrow, individually and collectively. This handbook has three parts. Part 1 is a classification of materials for which this Handbook has been prepared. The materials are those produced by media and information offices, private or public, for Philippines' National Centennial Commission as well as the Centennial's events and activities. Part 2 provides checklist by which to review verbal and visual language, symbols, images, and other cultural material touching on history. Part 3 is a listing of Filipino values that motivated the Philippine Revolution and are essential to our future. A communicator may use to accentuate them. (How to Use this Handbook).
Cover title.
Keywords: Philippines -- Centennial celebrations, etc. -- Handbooks, manuals, etc